Voice outcome after type-1 thyroplasty for unilateral vocal cord paralysis: our experience at tertiary care hospital - Ali, Ihsan; Khalid, Faheem; Shafi, Omar Mohammad; Makhdoomi, Owais (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Vocal cord paralysis is a clinical sign caused by paralysis of intrinsic muscles of larynx due to dysfunction of recurrent laryngeal nerve or injury to the vagus nerve. One of the common and effective methods of medialization is by using silicone implants. This study was aimed at prospectively assessing and analysing the vocal outcomes and quality of life of patients in type 1 medialization thyroplasty using silicone implants. Methods: Prospective study of 18 months was done on 17 patients with unilateral vocal cord paralysis. Surgical procedure for the patients was standardized by using silicon implant to medialize the cord. The parameters used for the pre and post treatment objective analysis were stroboscopic analysis, psychoacoustic evaluation, maximum phonation time (MPT) and patient’s self-assessment. Results: In our study all 17 patients with unilateral vocal cord paralysis who were subjected to vocal cord medialization using silicone implant showed a statistically highly significant improvement in all the parameters of assessment. The mean preoperative MPT was 7.260 and post-operative MPT showed significant improvement and was 17.428 seconds. mean preoperative GRBAS score was 11.695 and post-operative was 3.826. Similarly, pre op vocal handicap index was 31.173 which decreased significantly after the procedure was 7.695. Conclusions: In the present study, we obtained favourable results of medialization thyroplasty as expressed by objective analysis of voice including GRABS score and acoustic analysis as well as maximum phonation time apart from traditional voice recording.